2006
DOI: 10.1542/peds.2006-0313
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Nature of Adverse Events During Pediatric Sedation/Anesthesia for Procedures Outside the Operating Room: Report From the Pediatric Sedation Research Consortium

Abstract: Our data indicate that pediatric sedation/anesthesia for procedures outside the operating room is unlikely to yield serious adverse outcomes in a collection of institutions with highly motivated and organized sedation services. However, the safety of this practice depends on the systems' ability to manage less serious events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
328
3
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(350 citation statements)
references
References 16 publications
15
328
3
4
Order By: Relevance
“…Although there were initial concerns about providing sedation in such settings for invasive procedures, our own experience and that of others have shown few safety concerns. The Pediatric Sedation Research Consortium reported a large series of 30,037 sedation encounters from 26 centers, with data submitted on a variety of pediatric procedures performed under sedation or anesthesia outside the operating room (Cravero et al, 2006). This study demonstrated the overall safety of such procedures, with no deaths and only one cardiopulmonary resuscitation event.…”
Section: Nuts and Bolts: Sedation Or Anesthesia For The Pediatric Renmentioning
confidence: 91%
See 1 more Smart Citation
“…Although there were initial concerns about providing sedation in such settings for invasive procedures, our own experience and that of others have shown few safety concerns. The Pediatric Sedation Research Consortium reported a large series of 30,037 sedation encounters from 26 centers, with data submitted on a variety of pediatric procedures performed under sedation or anesthesia outside the operating room (Cravero et al, 2006). This study demonstrated the overall safety of such procedures, with no deaths and only one cardiopulmonary resuscitation event.…”
Section: Nuts and Bolts: Sedation Or Anesthesia For The Pediatric Renmentioning
confidence: 91%
“…This approach is not necessarily the case worldwide and, in fact, a recent audit in the United Kingdom (Hussain et al, 2010) showed 6 of 11 centers routinely using general anesthesia for pediatric kidney biopsies. Intravenous ''conscious'' sedation, sometimes termed ''deep'' procedural sedation, is usually administered by a nurse or physician who has acquired expertise in various sedation techniques and certification in pediatric advanced life support (Cravero et al, 2006;Mason et al, 2009). The patients should receive continuous cardiorespiratory monitoring throughout the procedure.…”
Section: Nuts and Bolts: Sedation Or Anesthesia For The Pediatric Renmentioning
confidence: 99%
“…These guidelines acknowledge and seek to address the increased risks of potentially life-threatening adverse events in these clinical scenarios, even in experienced hands. The Pediatric Sedation Research Consortium has reported one cardiac arrest in a cohort of 30,037 children receiving sedation [12], and 2 in a later cohort of 49,836 children sedated with propofol [13], but with no deaths. Nevertheless, deaths do still occur and continue to be reported [14].…”
Section: Brief Communication (Original)mentioning
confidence: 99%
“…A listing of but a few of the many reports providing a critical look at sedation in dentistry is included in the references below for the interested reader [55][56][57][58][59].…”
Section: Issn: 2380-0569mentioning
confidence: 99%